Composition and diversity of soil microbial communities in the alpine wetland and alpine forest ecosystems on the Tibetan Plateau - Wang, Xiaojie; Zhang, Zhichao; Yu, Zhiqiang; Shen, Guofeng; Cheng, Hefa; Tao, Shu (The Science of the total environment, 2020)
While the composition and diversity of soil microbial communities play a central and essential role in biogeochemical cycling of nutrients, they are known to be shaped by the physical and chemical properties of soils and various environmental factors. This study investigated the composition and diversity of microbial communities in 48 samples of seasonally frozen soils collected from 16 sites in an alpine wetland region (Lhasa River basin) and an alpine forest region (Nyang River basin) on the Tibetan Plateau using high-throughput sequencing that targeted the V3-V4 region of 16S rRNA gene. The dominant soil microbial phyla included Proteobacteria, Acidobacteria, and Actinobacteria in the alpine wetland and alpine forest ecosystems, and no significant difference was observed for their microbial composition. Linear discriminant analysis Effect Size (LEfSe) analysis showed that significant enrichment of Hymenobacteraceae and Cytophagales (belonging to Bacteroidetes) existed in the alpine wetland soils, while the alpine forest soils were enriched with Alphaproteobacteria (belonging to Proteobacteria), suggesting that these species could be potential biomarkers for alpine wetland and alpine forest ecosystems. Results of redundancy analysis (RDA) suggest that the microbial community diversity and abundance in the seasonally frozen soils on the Tibetan Plateau were mainly related to the total potassium in the alpine wetland ecosystem, and available potassium and soil moisture in the alpine forest ecosystem, respectively. In addition, function prediction analysis by Tax4Fun revealed the existence of potential functional pathways involved in human diseases in all soil samples. These results provide insights on the structure and function of soil microbial communities in the alpine wetland and alpine forest ecosystems on the Tibetan Plateau, while the potential risk to human health from the pathogenic microbes in the seasonally frozen soils deserves attention. [Display omitted] •Bacterial α-diversity decreased with altitude in the Tibetan alpine wetland soils.•Bacterial β-diversity was significantly different in alpine wetland and forest soils.•Wetland and forest ecosystems showed little difference in soil microbial composition.•Total/available K and moisture influenced the structure of soil microbial communities.•Potential functional pathways involved in human disease were identified in the soils.